"Neither here, nor there": Belonging, ambiguity, and the struggle for recognition among "in-between" Finnish Kaale. Issue 2 (December 2018) - Roman, Raluca Bianca
Abstract : Based on extended fieldwork among Finnish Kaale, this article focuses on the experience of belonging among individuals who do not fit within narrow cultural or ethnic categories, and who regularly navigate between their diverse and often multiple attachments: people born into mixed marriages (of Roma and non-Roma partnerships), women who chose to abandon elements of what are considered central proofs of their community belonging (dress, customs, age/gender hierarchy) or individuals who grew up detached from the central unit of solidarity (the family). Some of the contradictions these individuals embody, and the continuous crossing of invisible boundaries, highlight not only the complexity of "group belonging, " but the struggles that lie within attempts of attachment to others. This article, therefore, adds to previous discussions of a so-called "Roma identity" (or identities) and goes beyond arguments of cultural distinctiveness or marginalization, aiming to highlight the ways in which individuals themselves continuously assess processes of categorization and self-categorization.